Panel of Regulatory miRNAs for Blood Coagulation under Normoxic and Hypoxic Conditions - Hembrom, Anju Angelina; Ghosh, Nilanjana; Kumar, Vinay; Garg, Iti; Ganju, Lilly; Srivastava, Swati (Defence Life Science Journal, 2022)
Abnormal blood coagulation may lead to venous thromboembolism (VTE), a complex multifactorial disease. Hypoxia (oxygen deprivation) is a major factor disturbing the blood hemostasis and predisposing the body towards coagulation and VTE. Pathophysiology of VTE can be attributed to post-transcriptional gene regulation by microRNAs (miRNAs). The present study identified regulatory miRNAs involved in causing blood coagulation under normoxic and hypoxic conditions. Meta-analysis was performed, following PRISMA guidelines, for identifying miRNAs involved in blood coagulation pathway. Studies evaluating miRNAs from circulating blood as potential biomarkers of VTE were selected. A total of 16 studies met selection criteria and 8 having complete statistical information were selected for analysis. Study of blood coagulation mechanism under hypoxic conditions involved in-silico search within highly cited databases to identify miRNAs commonly regulating genes of hypoxia-inducible factor (HIF) family and coagulation pathway. Further bio-informatics approaches were employed to identify potential biomarker candidates. Meta-analysis revealed a panel of 12 miRNAs; two members of miR-27 family, hsa-miR-27a and hsa-miR-27b; two members of miR-320 family, hsa-miR-320a and hsa-miR-320b, hsa-miR-1233, hsa-miR-134, hsa-miR-424-5p, hsa-miR-221, hsa-miR-28-3p, hsa-miR-136-5p, hsa-miR-374-5p and hsa-miR-338-5p involved in blood coagulation under normoxic conditions. Besides these, present in-silico analysis identified a set of 5 miRNAs including hsa-miR-4667-5p, hsa-miR-6815-3, hsa-miR-4433a-3p, hsa-miR-6735-5p and hsa-miR-6777-3p which predominantly regulate genes that facilitate both coagulation and response to hypoxic stress. The present study generated a panel of regulatory miRNAs potentially involved in the process of blood coagulation under both normoxic and hypoxic conditions, which may serve as putative epigenetic biomarkers for coagulation.